Penatalaksanaan Holistik pada Pasien Anak dengan Demam Tifoid Melalui Pendekatan Kedokteran Keluarga - Andria Novita Sari (CV. Jasa Sukses Abadi, 2020)
Typhoid fever is an infectious disease caused by Salmonella typhi. Transmission of the disease is usually through contaminated food or water. Poor hygiene and healthy behavior can increase the risk of typhoid fever. Early and adequate treatment can reduce complications and recurrence. This study is a case report. Patient Ms.F, 10 years old, was diagnosed with typhoid fever. Internal risk factors for patient were the habit of careless street food snacking and lack of typhoid fever knowledge. External factors were unoptimized habit of clean and healthy lifestyles and low-income family. The patient lives with her parents and five siblings. On history taking, physical examination, and laboratories found seven days of fever accompanied by nausea and vomiting 4−5x / day, temperature of 39.0oC, typhoid tongue (+), tenderness in the epigastrium, and a significant rise in titer in the Widal serology test. Medical treatment with chloramphenicol 4x500mg, paracetamol 3x500mg, and domperidone 3x10mg. Holistic and comprehensive management of Ms.F's patients has been carried out by providing counseling about typhoid fever, prevention efforts, and implementation of clean and healthy lifestyles and the importance of preventive measures to prevent complications of the disease to increase the knowledge of patients and their families.